Transcriptome analysis reveals the function of TLR4-MyD88 pathway in immune response of Crassostrea hongkongensis against Vibrio Parahemolyticus - Jiayu Chen; Jinji Lin; Feifei Yu; Zhiming Zhong; Qiwen Liang; Huanying Pang; Siyu Wu (Aquaculture Reports, 2022)
Crassostrea hongkongensis (C. hongkongensis) is an important economic shellfish in marine aquaculture, but suffers from severe infection of Vibrio parahaemolyticus (V. Parahemolyticus). The study on immune strategy against Vibrio infection will help to enhance the disease resistance of C. hongkongensis. In this study, after V. parahaemolyticus challenge, the immune enzyme activities and transcriptome were analyzed to explain the immune strategy of C. hongkongensis. The immune enzyme activities analysis showed that all of superoxide dismutase (SOD), catalase (CAT), lysozyme (LZM) activities and malondialdehyde (MDA) content were significantly increased among 3 and 12 h post-infection, indicating that V. parahaemolyticus had stimulated the immune response of C. hongkongensis. Transcriptome analysis showed that a total of 636,295,318 clean readings were generated from the libraries of control and infection groups. Comparing with the control groups (C0h), 147 differentially expressed genes (DEGs) were identified in T3h group, 392 DEGs in T6h group, 47 DEGs in T12h group, and 423 DEGs in T24h group. The time-series expression profiles of DEGs showed that the rising and failing trends were significantly enriched in 2 clusters, including 158 DEGs. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that immune-related DEGs were annotated into 20 categories, including Toll and Imd signaling pathway, IL-17 signaling pathway, Toll like receptor (TLR) pathway and c-type lectin receptor signaling pathway. Since multiple immune-related DEGs were enriched in TLR signal pathway, qRT-PCR was employed to validate the expression of genes in TLR pathway. The qRT-PCR results showed that all of six detected genes were significantly upregulated, including TLR4, MyD88, IRAK4, TRAF6, IL17 and COX2. The data indicated that TLR4-MyD88 pathway took part in the immune response of C. hongkongensis against Vibrio infection.